Pengaruh Kesadaran Wajib Pajak, Pengetahuan Perpajakan, dan Sanksi Perpajakan Pada Kepatuhan Wajib Pajak UMKM - Perdana, Efrie Surya; Dwirandra, A.A.N.B (E-Jurnal Akuntansi; Vol 30 No 6 (2020), 2020)
This study aims to determine the effect of awareness of taxpayers, tax knowledge and tax sanctions on UMKM taxpayer compliance registered at Tabanan Primary Tax Office. This research uses primary data and secondary data. Primary data were obtained from responses to a series of statements in the form of questionnaires to UMKM taxpayers registered at the Tabanan Primary Tax Office, while secondary data was in the form of data on the number of UMKM taxpayers registered at the Tabanan Primary Tax Office. The sample in this study was determined using the stratified random sampling method. After fulfilling the classical assumption test, the data are then analyzed using multiple linear regression analysis techniques. The results of this study indicate that taxpayer awareness, tax knowledge, and tax sanctions have a positive and significant effect on tax compliance of UMKM registered at the Tabanan Primary Tax Office. Keywords: Taxpayer Awareness; Taxation Knowledge; Tax sanctions; UMKM Taxpayer Compliance.